Morphological Analysis of Compound Words Used in Colleen Hoover's It Ends with Us and Delia Owens' Where the Crawdads Sing Novels - Syafira Dwi Maharani; Refnaldi Refnaldi (English Language and Literature, 2022)
This study examined the types, and the patterns of compound words used in It Ends with Us and Where the Crawdads Sing novel. This research employed McCarthy’s (2002) types and patterns of compound words to determine how the words are formed. This research used a descriptive quantitative methodology. The data were the compound words found in 35 chapters of It Ends with Us and 57 chapters of Where the Crawdads Sing novels. There were 146 compound words in It Ends with Us and 278 compound words in Where the Crawdads Sing novel. The findings show that a compound noun is the most dominant compound type that occurs in both novels. The compound words found in both novels were formed by more patterns than the ones that were proposed by McCarthy (2002). The authors of both novels write the compound words by adding a hyphen and more words to describe the details of what is being described in the story. It can be concluded that It Ends with Us novel focuses more on the occurrence of repeated words, whereas Where the Crawdads Sing novel focuses more on variations in patterns.